The Problem of Malaria and Its Eradication System in Tanjungpinang During The Dutch Colonial Era - Saumia, Zulfa; Erniwati, Erniwati; Syafrina, Yelda (Indonesian Historical Studies, 2023)
Malaria outbreaks are a health problem that is not easy to overcome. Its spread and prevention have been an important issue ever since the Dutch colonial period. This article explains how the malaria outbreak became an important issue during the colonial period in the Tanjung Pinang area, one of the areas where the endemic spread and was quite worrying due to the large number of fatalities. This article also explains how this endemic occurred and was overcome by the Chinese population in Tanjung Pinang, as well as the handling of the colonial government. This article uses existing historical sources to describe the problem of endemic diseases and efforts to eradicate them during the Dutch colonial period. The main aim of this paper is to examine the seriousness of endemic issues and their causes in the region and describe how the colonial government resolved them. There has been significant progress in malaria eradication, and the understanding of the causes of malaria and the selected eradication methods reflect scientific advances and economic considerations.